2011
DOI: 10.1007/s11120-011-9624-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of carboxysome shell proteins

Abstract: Carboxysomes are metabolic modules for CO 2 fixation that are found in all cyanobacteria and some chemoautotrophic bacteria. They comprise a semi-permeable proteinaceous shell that encapsulates ribulose-1,5-bisphosphate carboxylase/oxygenase (RuBisCO) and carbonic anhydrase. Structural studies are revealing the integral role of the shell protein paralogs to carboxysome form and function. The shell proteins are composed of two domain classes: those with the bacterial microcompartment (BMC; Pfam00936) domain, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
143
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 116 publications
(145 citation statements)
references
References 46 publications
2
143
0
Order By: Relevance
“…This assumption is supported by measurements of millimolar RuBP in S. elongatus (37), but it remains unclear how RuBP enters the carboxysome (49,56). Similarly, we assume that O 2 enters the carboxysome quickly enough to equalize concentrations across the carboxysome shell (SI Appendix), that is, that the CCM is not an "oxygen-blocking mechanism.…”
Section: S Elongatus Cyotosolic Ph Is Within the Optimal Range For Ccmmentioning
confidence: 73%
See 2 more Smart Citations
“…This assumption is supported by measurements of millimolar RuBP in S. elongatus (37), but it remains unclear how RuBP enters the carboxysome (49,56). Similarly, we assume that O 2 enters the carboxysome quickly enough to equalize concentrations across the carboxysome shell (SI Appendix), that is, that the CCM is not an "oxygen-blocking mechanism.…”
Section: S Elongatus Cyotosolic Ph Is Within the Optimal Range For Ccmmentioning
confidence: 73%
“…Throughout the text, we assumed that the carboxysome is equally permeable to CO 2 and HCO 3 − . However, recent structures of carboxysome shell proteins offer a potential mechanism for differential permeability of CO 2 and HCO 3 − : The pores of shell proteins typically carry positive charge, which might increase the rate of HCO 3 − transit relative to CO 2 (12,49). Indeed, recent experimental evidence suggests that protein compartments can be selectively permeable (50,51).…”
Section: S Elongatus Cyotosolic Ph Is Within the Optimal Range For Ccmmentioning
confidence: 99%
See 1 more Smart Citation
“…Both ␣-and ␤-types of carboxysome shells contain a minor component, CsoS4 or CcmL, respectively, that belongs to the EutN domain family (pfam03319); CsoS4 and CcmL form pentamers proposed to serve as the vertices of the icosahedron (1,3).…”
mentioning
confidence: 99%
“…A recent bioinformatic survey revealed that ϳ20% of sequenced bacterial genomes, from 13 bacterial phyla, have genes coding for both protein families, suggesting that the potential for forming compartments enclosed by carboxysome-like shells is widespread in the bacterial domain (11). The functions of some of these have been experimentally determined (12)(13)(14)(15), but for most the only available functional information is derived from the annotations of the genes clustering with shell protein genes (3,11). Collectively, carboxysomes and these (presumably) architecturally similar organelles are known as BMCs.…”
mentioning
confidence: 99%